The Link Between Glycemic Control and Complications after Cataract Surgery in Type 2 Diabetes: A Systematic Review: Glycemic Control and Complications after Cataract Surgery - alqahtani, Saeed; Alshehri, Abdulaziz Ibrahim; Almakrami, Mohammed Ibrahim A; Al Rashah, Ahmed Mohseen Y; Alqahtani, Fatimah Dulaym; Al Murthimah, Ali Mohammed A; Al Baalharith, Mohammed Hadi S; Al Abyah, Ahmed Hussain A; Al Rashah, Hussain Ahmed S; Al Sulayyi, Turki Saeed M; Al Sidran, Ibrahim Khalid; Al Yassain, Abdulrahman Mohammed M (Saudi Medical Horizons Journal, 2025)
Cataract surgery is a common procedure in patients with type 2 diabetes mellitus (T2DM), who face a higher risk of postoperative complications. Glycated hemoglobin (HbA1c) is a standard measure of glycemic control, but its role as a predictor for surgical outcomes in ophthalmology remains unclear, leading to debate over preoperative HbA1c thresholds. This systematic review aimed to synthesize the evidence on the association between preoperative HbA1c levels and the risk of complications following cataract surgery in patients with T2DM. A systematic search was conducted following PRISMA guidelines across PubMed/MEDLINE, Web of Science, SCOPUS, and Embase. Observational studies investigating the link between preoperative HbA1c and postoperative complications in T2DM patients were included. Two independent reviewers performed study selection, data extraction, and risk of bias assessment using the Newcastle-Ottawa Scale. Twelve studies were included. The evidence revealed a complication-specific relationship. Elevated preoperative HbA1c (e.g., >7%) was a significant independent risk factor for cystoid macular edema (relative risk 2.01) and diabetic macular edema, supported by a clear pathophysiological link. Conversely, large-scale studies found no significant association between HbA1c and the risk of acute endophthalmitis. Several studies indicated that overall diabetes severity (e.g., renal function, complication burden) was a more robust predictor of surgical risk than glycemic control. The relationship between preoperative HbA1c and post-cataract surgery complications is not uniform. A comprehensive preoperative assessment that includes retinal status, renal function, and overall diabetes complication severity is recommended for individualized risk stratification and optimized surgical outcomes.